1995
DOI: 10.1016/s0022-5347(01)67289-6
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Arrangement of Collagen and Elastin Fibers in the Human Urinary Bladder: A Scanning Electron Microscopic Study

Abstract: To clarify the arrangements of collagen and elastin fibers of the urinary bladder, we examined 9 human (male, aged 42 to 72) urinary bladders by scanning electron microscopy with chemical digestion methods. The mucosal layer was divided into 3 portions according to the collagen arrangement: the superficial portion interwoven densely by collagen fibrils, the middle portion layered by flat bundles of collagen fibrils and the deep portion made of a loose network of twisted collagen bundles. In the muscular layer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 20 publications
4
41
0
4
Order By: Relevance
“…Previous studies have suggested that elastic tissue is a normal component in the genito-urinary region [1,11]. Our results showed that the capsule of the dog prostate contain a large number of elastic membranes of different thicknesses forming one thick layer and partially integrated in the muscle layer of the capsule.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Previous studies have suggested that elastic tissue is a normal component in the genito-urinary region [1,11]. Our results showed that the capsule of the dog prostate contain a large number of elastic membranes of different thicknesses forming one thick layer and partially integrated in the muscle layer of the capsule.…”
Section: Discussionsupporting
confidence: 57%
“…The fibres were seen to be associated with the longitudinal smooth muscle bundles of the urethra and urinary bladder of the guinea pig [10,11]. D a s s e t al.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…en la mucosa en tres capas: una capa superficial de fibras no orientadas que forma un entretejido denso en el que se apoya el urotelio, una capa media de fibras delicadamente entrelazadas y apiladas de diverso grosor y una capa profunda constituida por una delicada red de fibras retorcidas 13 .…”
Section: Estructura Del Tracto Urinario Inferiorunclassified
“…Therefore, this missing organizational information about bladder wall morphology and microstructure is acquired from thin samples using optical microscopy techniques. 10,12 Polarized light imaging in bulk intact tissues is beginning to be used for quantitative assessment of morphology in biological tissues. [13][14][15][16][17][18][19][20] When the tissue polarimetric properties are properly decoupled with the help of polarization data analysis technique known as polar Mueller matrix decomposition, 21,22 a particular parameter known as retardance emerges.…”
Section: Introductionmentioning
confidence: 99%